Efficacy and safety of small molecule oral medications for psoriatic arthritis: a network meta-analysis of randomized controlled trials - Ya-Chu Tsai; Chen-Yiu Hung; Tsen-Fang Tsai (Therapeutic Advances in Musculoskeletal Disease)
Background: Although there have been network meta-analyses (NMAs) regarding the efficacy and safety of targeted immunotherapy for psoriatic arthritis, most of them primarily focus on biologics. However, small molecules and biologics have many differences in properties and onset time. This NMA put emphasis on small molecule drugs and incorporates medications including upadacitinib and deucravacitinib, which have been less compared previously. Objective: To compare the efficacy and safety of small molecule drugs (apremilast, deucravacitinib, tofacitinib, and upadacitinib) in active psoriatic arthritis (PsA) using NMA. Design: This study was conducted and reported following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension Statement for Network Meta-Analyses (PRISMA-NMA), with relevant articles identified through searches across electronic databases. Data sources and methods: Databases including PubMed, Cochrane Library, and ClinicalTrial.gov were searched. Randomized controlled trials (RCTs) of targeted synthetic small molecules for PsA controlled by either placebo or active comparators within weeks 12–16 were eligible. A frequentist framework and a random-effect model were employed for the analysis. The revised Cochrane risk-of-bias tool for RCTs was used to assess the quality of the enrolled studies. Results: A total of 9 RCTs involving 3699 patients were analyzed. Apremilast 30 mg bid, deucravacitinib 6 mg and 12 mg qd, tofacitinib 5 mg bid, and upadacitinib 15 mg qd all demonstrated superior efficacy over placebo in achieving American College of Rheumatology (ACR) 20/50/70, Psoriasis Area and Severity Index (PASI) 75, and Health Assessment Questionnaire-Disability Index (HAQ-DI) scores at weeks 12–16. When compared to adalimumab, upadacitinib achieved borderline superiority in PASI 75 at week 12 (risk ratio (RR) = 1.20, 95% confidence interval (CI): 1.02–1.40). Among the four medications studied, only deucravacitinib showed significantly better HAQ-DI scores compared to apremilast (RR = −0.16, 95% CI: −0.29 to −0.02), with no statistically significant differences observed in other parameters. Conclusion: All four small molecule oral medications exhibited superior efficacy to placebo and comparable safety profiles. Across different assessment criteria, including ACR 50, ACR 70, PASI 75, or HAQ-DI, deucravacitinib 12 mg and upadacitinib consistently ranked in the top two positions.